2020
DOI: 10.1590/1516-4446-2019-0753
|View full text |Cite
|
Sign up to set email alerts
|

N-acetylcysteine as an adjunctive treatment for smoking cessation: a randomized clinical trial

Abstract: Objective: This randomized controlled trial examined the efficacy and safety of N-acetylcysteine as an adjunctive treatment for smoking cessation. Methods: Heavy smokers were recruited from smoking cessation treatment for this 12-week randomized controlled trial. Eligible tobacco use disorder outpatients (n=34) were randomized to N-acetylcysteine or placebo plus first-line treatment. Abstinence was verified by exhaled carbon monoxide (CO exh). The assessment scales included the Fagerströ m Test for Nicotine De… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 33 publications
0
6
0
1
Order By: Relevance
“…Commonly, studies have indicated that NAC acts as a promising agent for the treatment of substance use disorders, whereas the drug has the ability to restore the transmission of the prefrontal glutamate from the nucleus accumbens, reducing relapses. Furthermore, a randomized clinical trial examining the efficacy of NAC, in adjuvant treatment for smoking cessation, found that NAC (1800 mg) associated with first-line treatment was able to significantly reduce exhaled carbon monoxide ( p < 0.01); the intervention group showed no withdrawal symptoms, depression, or anxiety and had a significant decrease in the levels of the soluble tumor necrosis factor 2 receptor (sTNF-R2) [ 105 ].…”
Section: Clinical Indicationsmentioning
confidence: 99%
“…Commonly, studies have indicated that NAC acts as a promising agent for the treatment of substance use disorders, whereas the drug has the ability to restore the transmission of the prefrontal glutamate from the nucleus accumbens, reducing relapses. Furthermore, a randomized clinical trial examining the efficacy of NAC, in adjuvant treatment for smoking cessation, found that NAC (1800 mg) associated with first-line treatment was able to significantly reduce exhaled carbon monoxide ( p < 0.01); the intervention group showed no withdrawal symptoms, depression, or anxiety and had a significant decrease in the levels of the soluble tumor necrosis factor 2 receptor (sTNF-R2) [ 105 ].…”
Section: Clinical Indicationsmentioning
confidence: 99%
“…31 Relatedly, a similar clinical approach revealed that administration of another smoking cessation aid, bupropion, combined with NAC reduced several inflammatory and metabolic symptoms in heavy smokers. 49 These clinical results, combined with our preclinical data, suggest that sequentially combining VRN and NAC is a promising approach to reduce smoking and relapse.…”
Section: Translational Utility and Mechanismsmentioning
confidence: 73%
“…The possibility of combining NAC and VRN to treat nicotine addiction (tobacco use disorder) in humans has advanced only as far as a small open safety trial of non‐treatment‐seeking smokers that revealed no adverse effects of the drug combination and a modest reduction in cigarette use 31 . Relatedly, a similar clinical approach revealed that administration of another smoking cessation aid, bupropion, combined with NAC reduced several inflammatory and metabolic symptoms in heavy smokers 49 . These clinical results, combined with our preclinical data, suggest that sequentially combining VRN and NAC is a promising approach to reduce smoking and relapse.…”
Section: Resultsmentioning
confidence: 99%
“…Machado et al en el 2020 realizó un ensayo controlado aleatorizado de 12 semanas en 39 personas fumadoras que estaban en tratamiento conjunto con psicoterapia y bupropión. No se documentaron cambios significativos en el craving, pero si una mejora en el abandono del hábito de fumar con una reducción significativa en los niveles de nicotina (47). Estos resultados son consistentes con lo encontrado previamente por Shulte (2017) quien en un ensayo clínico con 45 personas que buscaban dejar de fumar y sometidos a una dosis de NAC de 2400 mg por 14 días, encontró una disminución del número de cigarrillos fumados y disminución en los niveles de nicotina al igual que disminución del deseo de consumo (48).…”
Section: Evidencia De La Nac En El Manejo Del Craving a Tabacounclassified